PSX-1 A newly developed pectinase from Aspergillus terreus enhanced feed utilization and milk production of Damascus goats fed pectin-rich diet - Anele, Uchenna (J Anim Sci, 2020)
A newly developed pectinase from Aspergillus terreus was compared with a commercially available pectinase at 600 IU/kg feed. Thirty (one-week postpartum) Damascus goats stratified by previous milk production, body weight and parity were divided into three experimental treatments. Does were fed a basal diet containing concentrates, orange silage, sugar beet pulp and wheat straw at 50:20:20:10, respectively with (a newly developed pectinase or commercial pectinase) or without a supplement (control treatment). No difference (P >0.05) was noted for feed intake but the newly developed pectinase increased (P < 0.01) nutrient digestibility, diet nutritive value and milk production efficiency more than the other treatments. Out of all the blood parameters, only serum glucose was affected by the treatments with highest (P = 0.025) value noted for the new pectinase. Similarly, the new pectinase increased daily milk production (P < 0.005) and the concentrations of milk components compared to the other two treatments. Additionally, pectinase (both the commercial and new) inclusion increased (P < 0.05) the concentrations of total conjugated linoleic acid and unsaturated/saturated fatty acids ratio, and decreased atherogenic index (P = 0.01) compared with control treatment. It is concluded that the supplementation of the diet of lactating goats with pectinase at 600 IU/kg feed will enhance feed digestion and milk production. The newly developed pectinase performed better than the commercial pectinase.